2013
DOI: 10.1063/1.4809991
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic scaling of dynamics in polymer melts: Predictions from the generalized entropy theory

Abstract: Many glass-forming fluids exhibit a remarkable thermodynamic scaling in which dynamic properties, such as the viscosity, the relaxation time, and the diffusion constant, can be described under different thermodynamic conditions in terms of a unique scaling function of the ratio ρ γ /T , where ρ is the density, T is the temperature, and γ is a material dependent constant. Interest in the scaling is also heightened because the exponent γ enters prominently into considerations of the relative contributions to the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

7
2

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 63 publications
10
42
0
Order By: Relevance
“…In particular, the chains in the more realistic model have the structure of poly(n-α-olefins) where the terminal segments on the side chains are assigned different, specific van der Waals interaction energies with other united atom groups. The greater realism introduced into the LCT and the GET by this new model enables testing the limits of validity of the present model with a single monomer averaged van der Waals energy [9,10,22,[25][26][27][28][29][30]. In addition, the subsequent work will study how the variation of the specific interactions can be used to exert greater control over the properties of designed materials.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the chains in the more realistic model have the structure of poly(n-α-olefins) where the terminal segments on the side chains are assigned different, specific van der Waals interaction energies with other united atom groups. The greater realism introduced into the LCT and the GET by this new model enables testing the limits of validity of the present model with a single monomer averaged van der Waals energy [9,10,22,[25][26][27][28][29][30]. In addition, the subsequent work will study how the variation of the specific interactions can be used to exert greater control over the properties of designed materials.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the new extension of the LCT is combined with the AG theory [16,17], thereby providing a similar generalization of the GET to describe polymer glass formation. Moreover, the greater realism introduced into the LCT and the GET by the new physical model enables testing the limits of validity of the simpler LCT model with a single monomer averaged van der Waals energy [13,14,[18][19][20][21][22][23][24][25], which is also discussed in detail in the present paper.…”
Section: Introductionmentioning
confidence: 99%
“…Tsolou et al [63] found γ = 2.8 from power-law density scaling of simulation data of a united atom model of cis-1,4-polybutadiene. A possible explanation for this low value of γ has been given by Xu [64] who showed using the generalized entropy theory that polymer rigidity significantly decreases the density scaling exponent γ. Xu quantified polymer rigidity y the bending energy of the angle between two bonds.…”
Section: A Generating Isomorphsmentioning
confidence: 99%